Estrategias didácticas innovadoras para una educación inclusiva en estudiantes con problemas de aprendizaje (2021)
Providing a quality education currently requires proposing didactic strategies to attend an inclusive education and articulate them to the PEI, aimed at students who present learning problems of the IED Quinto Centenario de Santa Marta. In this order of ideas, it is established that from a methodological perspective a mixed paradigm was determined under a sequential mixed approach of an exploratory-descriptive nature and with a non-experimental, transversal or transsectional design with a representative population of 49 teachers and 26 students. Instruments such as the survey and the interview were used for their reliability, validity and objectivity which allowed to obtain results that were analyzed and interpreted in order to establish mechanisms for solving the difficulties present in those who lead and accompany or guide learning, without neglecting the development of skills and competencies in inclusive environments where equal opportunities are favored , the integral, updated and contextualized training that demands any curricular structure appropriate to an institutional educational process.